2020
DOI: 10.3390/toxins12060357
|View full text |Cite
|
Sign up to set email alerts
|

Multi Mycotoxin Determination in Dried Beef Using Liquid Chromatography Coupled with Triple Quadrupole Mass Spectrometry (LC-MS/MS)

Abstract: Dried beef meat, a locally processed meat from the cow, is vulnerable to contamination by mycotoxins, due to its exposure to the environmental microbiota during processing, drying, and point of sale. In this study, 108 dried beef samples were examined for the occurrence of 17 mycotoxins. Samples were extracted for mycotoxins using solid-liquid phase extraction method, while liquid chromatography coupled with triple quadrupole mass spectrometry (LC-MS/MS) via the dilute and shoot method was used to analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The research was carried out on the number of dairy cows in the conditions of the economy of the Sumy region. In the study of beef cattle, other results can be obtained, which is confirmed by the studies of other authors [16].…”
Section: Resultssupporting
confidence: 77%
“…The research was carried out on the number of dairy cows in the conditions of the economy of the Sumy region. In the study of beef cattle, other results can be obtained, which is confirmed by the studies of other authors [16].…”
Section: Resultssupporting
confidence: 77%
“…The lowest LOD and LOQ values were achieved with STC and AFB 1 and the highest with CPA. For example, the multi-mycotoxin LC–MS/MS method of Dada et al [ 35 ], used to analyse dried beef, which employs a solid–liquid extraction, resulted in the following LOD values: OTA 0.13 μg/kg, AFB 1 2 μg/kg, CIT 18 μg/kg, CPA 7 μg/kg, and STC 8 μg/kg. The validation results showed that the method is suitable for studying the occurrence of STC, CIT, OTA, AFB 1 , and CPA in dry-cured meat products.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its contact with the ambient microbiota during processing, drying, and point of sale, dried meat is also prone to infection by fungi, which may in turn release mycotoxins. A study concluded that mycotoxins could be found in dried beef samples from Nigerian regions Igede and Ikole, in which mycotoxins are frequently linked to serious health issues ( 152 ). It was mentioned that continuous exposure to mycotoxins like cyclopiazonic acid (CPA), alpha zearalenone, aflatoxin, ochratoxin A, sterigmatocystin and tenuazonic acid could cause immunotoxic, hepatotoxic, and carcinogenic effects on multiple organs in the human body ( 152 ).…”
Section: Safety and Challenges Of Dried Meats And How To Prevent Themmentioning
confidence: 99%